2018
DOI: 10.1002/cctc.201801166
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of 2,5‐Disubstituted Pyrrolidine Alkaloids via A One‐Pot Cascade Using Transaminase and Reductive Aminase Biocatalysts

Abstract: A multi‐enzymatic cascade process involving transaminases (TAs) and reductive aminases (RedAms) to produce enantiomerically pure 2,5‐disubstituted pyrrolidine alkaloids from their respective 1,4‐diketones is reported. Several TAs were screened and the best results for diketone monoamination were obtained with an R‐selective TA from Mycobacterium chlorophenicum and with an S‐selective TA from Bacillus megaterium. Pyrroline reduction was best performed by a reductive aminase from Ajellomyces dermatitidis (AdRedA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 56 publications
0
24
0
1
Order By: Relevance
“…TAs containing the spuC gene from Pseudomonas species, in particular P. putida (Pp spuC), P. chlororaphis subsp. aureofaciens (Pc spuC) and P. fluorescens (Pf spuC), 28 and transaminases from Vibrio fluvialis (Vf), 29 Chromobacterium violaceum (Cv), 30 Alcaligenes denitrificans (Ad), 31 Bacillus megaterium (Bm) 32 and our high overproducing transaminase variant Bm S119G 33 were tested towards αsubstituted β-keto amides 2a-h finding that only BmTA and BmTA S119G were capable of reacting with the selected substrates ( Table 3). The desired enantiopure amines 3a-d,h were successfully synthesized by both (S)-transaminases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TAs containing the spuC gene from Pseudomonas species, in particular P. putida (Pp spuC), P. chlororaphis subsp. aureofaciens (Pc spuC) and P. fluorescens (Pf spuC), 28 and transaminases from Vibrio fluvialis (Vf), 29 Chromobacterium violaceum (Cv), 30 Alcaligenes denitrificans (Ad), 31 Bacillus megaterium (Bm) 32 and our high overproducing transaminase variant Bm S119G 33 were tested towards αsubstituted β-keto amides 2a-h finding that only BmTA and BmTA S119G were capable of reacting with the selected substrates ( Table 3). The desired enantiopure amines 3a-d,h were successfully synthesized by both (S)-transaminases.…”
Section: Resultsmentioning
confidence: 99%
“…The absolute configuration of the final products was determined due to the well-known (S)-selectivity of these two enzymes. 32,33 In order to demonstrate the applicability and reproducibility of this procedure, semipreparative biotransformations were set up. Hence, this would allow us to isolate and fully characterized the new diastereoenriched and enantiopure α-substituted βamino amides 3a-h. For this purpose, the robust ATA-025 was chosen as biocatalyst and DMSO was replaced with acetonitrile (MeCN) as cosolvent in order to facilitate the work-up protocols.…”
Section: Resultsmentioning
confidence: 99%
“…The thermodynamic limitations of the reaction may also be overcome by employing the reaction product in a cascade, and using this in‐situ product removal as a method for driving the transaminase reaction. There are a number of examples where a chemical transformation can be used to remove the product, however, more recent examples have coupled transaminases with other enzymes to produce heterocycles in one‐pot procedures …”
Section: Mature Reaction Classesmentioning
confidence: 99%
“…Studies have shown this can be circumvented using inexpensive amine donors in large excess such as isopropylamine (which in the formation of volatile acetone that drives the equilibrium to the desired product) or using sacrificial amine cosubstrates which displaces equilibria via ring aromatization or cyclisation (Gomm et al, 2016; Martínez-Montero et al, 2016; Galman et al, 2017). To date there are many examples that have demonstrated the use of ω-transaminases toward the production of industrially relevant amines, alkaloids, and other bioactive natural products (Guo and Berglund, 2017; Costa et al, 2018; Galman et al, 2018).…”
Section: Introductionmentioning
confidence: 99%